STEM-27. A PERIVASCULAR STEM CELL UNDERLIES VERTEBRATE MENINGEAL TUMORIGENESIS. (12th November 2021) - Choudhury, Abrar; Cady, Martha; Lucas, Calixto; Palikuqi, Brisa; Klein, Ophir; Hervey-Jumper, Shawn; Phillips, Joanna; Dickinson, Peter; Magill, Stephen; Bhaduri, Aparna; Crouch, Elizabeth; Raleigh, David
Abstract: BACKGROUND: Meningiomas are the most common primary intracranial tumors in humans and dogs, but biologic drivers and cell types underlying meningeal tumorigenesis are incompletely understood. Here we integrate meningioma single-cell RNA sequencing with stem cell approaches to define a perivascular stem cell underlying vertebrate meningeal tumorigenesis. METHODS: Single-cell RNA sequencing was performed on 57, 114 cells from 8 human meningiomas, 54, 607 cells from 3 dog meningiomas, and human meningioma xenografts in mice. Results were validated using immunofluorescence (IF), immunohistochemistry (IHC), and deconvolution of bulk RNA sequencing of 200 human meningiomas. Mechanistic and functional studies were performed using clonogenic and limiting dilution assays, xenografts, and genetically engineered mouse models. RESULTS: Copy number variant identification from human meningioma single cells distinguished tumor cells with loss of chr22q from non-tumor cells with intact chr22q. A single cluster distinguished by expression of Notch3 and other cancer stem cell genes had an intermediate level of loss of chr22q, suggesting this cluster may represent meningioma stem cells. In support of this hypothesis, pseudotime trajectory analysis demonstrated transcriptomic progression starting from Notch3 + cells and encompassing all other meningioma cell types. Notch3 + meningioma cells had transcriptomic concordance to mural pericytes, and IF/IHC of prenatal and adult human meninges, as well as lineage tracing using a Notch3-Cre ERT2 allele in mice, confirmed Notch3 + cells were restricted to the perivascular stem cell niche in mammalian meningeal development and homeostasis. Integrating human and dog meningioma single cells revealed Notch3 + cells in tumor and non-tumor clusters in dog meningiomas. Notch3 IF/IHC and cell-type deconvolution of bulk RNA sequencing showed Notch3 + cells were enriched in high-grade human meningiomas. Notch3 overexpression in human meningioma cells increased clonogenic growth in vitro, and increased tumorigenesis and tumor growth in vivo, decreasing overall survival. CONCLUSIONS: Notch3 + stem cells in the perivascular niche underlie vertebrate meningeal tumorigenesis.